6(x+1)/3=4X-1

Simple and best practice solution for 6(x+1)/3=4X-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+1)/3=4X-1 equation:


x in (-oo:+oo)

(6*(x+1))/3 = 4*X-1 // - 4*X-1

(6*(x+1))/3-(4*X)+1 = 0

(6*(x+1))/3-4*X+1 = 0

(6*(x+1))/3+(-4*3*X)/3+(1*3)/3 = 0

6*(x+1)-4*3*X+1*3 = 0

6*x-12*X+3+6 = 0

6*x-12*X+9 = 0

(6*x-12*X+9)/3 = 0

(6*x-12*X+9)/3 = 0 // * 3

6*x-12*X+9 = 0

6*x-12*X+9 = 0 // - 9-12*X

6*x = -(9-12*X) // : 6

x = (-(9-12*X))/6

x = (-(9-12*X))/6

See similar equations:

| -8+n/15=-9 | | 40+25=15+30 | | 9z-5-4z=-5 | | 20,50= | | 1/5+2 | | x/4+x/3=9/4 | | 5ln(x+3)=0 | | 3(2x-1)+4=5x | | 17=2x-15+x+8 | | -5y=4 | | 5x+1=2(2x+7) | | -12x+3x-109=143 | | 981+(45g*9)/(5*5)+9514=900000 | | 2+-5+-3=-6 | | -4(2y-3)-y=-2(y-5) | | 2+-5+-3= | | 41/45-1/27 | | 5x(6)-4= | | 3a-4a=4 | | -8=x/-7-10 | | -8=x/-7-10 | | X-6+x=10 | | -(-9)-5+(4)= | | -75+9x-x=69 | | 7/5*5/14 | | 42=7(x+4) | | 2.6(-2-8x)=-6-19.4x | | 0.50x+0.30(40)=0.25(134) | | x=(2y+5)-50 | | -2x^2+3x+4=13x-5x^2+1 | | 3+2z=5z-3-3z+6 | | 4c-19=17 |

Equations solver categories